ANALISIS MANAJEMEN KOMUNIKASI DISKOMINFOSTANDI DALAM MENINGKATKAN KUALITAS PELAYANAN PEMKOT BOGOR (STUDI KASUS APLIKASI SI BADRA) - Danil Sabilah; Tiara Puspanidra; Layung Paramesti Martha (UNIVERSITAS PAKUAN, 2021)
This study aims to describe how the communication management carried out by DISKOMINFOSTANDI in an effort to improve service quality through the Si Badra Application program. This research is a used of descriptive qualitative research methods. Data collection techniques through interviews, observation and documentation. The results showed that the communication management process carried out consisted of four stages, namely the analysis, planning, implementation, and control stages. In this stage DISKOMINFOSTANDI was less prepared in the implementation process, namely the training carried out. But it is very good in the other processes.